Exemplary Faculty Mentoring Programme - Tejonidhi, M. R.; Uma, B.; Swathi, H. Y.; Margaret, R. E.; Vinod, A. M. (Journal of Engineering Education Transformations, 2018)
Mentorship in institutions of higher education supports personal and professional development of faculty as they transit into new roles as teaching faculty. Mentorship programs attempt to address several types of common needs among new faculty, such as professional development, emotional support, intellectual community, role models, accountability, sponsorship, access to opportunities, and substantive feedback. New faculty members start their profession without any formal training in teaching. But teaching is a skill which can be best acquired through constant hard work, observation and interaction with senior faculty members. In an attempt to better train young faculty, they were made to choose a senior faculty as their mentor. This mentorship programme benefitted young faculty in several dimensions.